Green synthesis of carbon-doped zinc oxide using Garcinia mangostana peel extract: Characterization, photocatalytic degradation, and hydrogen peroxide production. (15th March 2023) - Huong, Le Minh; Cong, Che Quang; Dat, Nguyen Minh; Hai, Nguyen Duy; Nam, Nguyen Thanh Hoai; An, Hoang; Tai, Le Tan; Do Dat, Tran; Dat, Nguyen Tien; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: Recent decades have cordially observed unprecedented events in the fields of photochemistry for water remediation and fine chemical production. In this study, we reported sustainable methods to fabricate carbon-doped zinc oxides (ZnO–C) using aqueous Garcinia mangostana peel extracts as a carbon source. Via the reinforcement of ZnO–C crystal structures with the employment of calcination techniques, ZnO–C accentuated better crystallization with average nanoparticle size of 25–70 nm. In addition to the introduction of carbon, the samples revealed the doping of heteroatoms such as N, S, and P simultaneously in ZnO structures originating from the phytochemicals in the extracts. It is observed that ZnO–C sample calcinated at 700 °C for 1 h gives out the best results for photoactivity. Moreover, the fabricated ZnO–C-700-1.0 exhibited a near complete removal towards methylene blue and malachite green, while removal of rhodamine B was 62.13% after 120 min using commercial UV light irradiation under pH 11 with the usage of 50 mg of catalyst. Further investigations of H2 O2 photoproduction also validated the versatile application of the materials with the highest H2 O2 evolution rate reaching 38.75 mM/g.h. The techno-economical of H2 O2 production using ZnO–C reveals the scale-up viability of the process. Moreover, MB removal efficiency of 92.13% and H2 O2 production of 8.83 mM/g.h were observed for the optimal ZnO–C sample under visible light irradiation. Subsequently, these results reinforce the applicability of phytoextract as a green approach to reach sustainability for synthesis and modifying the optical structure of semiconducting materials for water remediation and H2 O2 production. Graphical abstract: Image 1 Highlights: Utilization of underutilized biomass as a carbon source for the synthesis of carbon-doped ZnO. Investigation effect of both calcination temperature and time on the structure of carbon-doped ZnO. Application in the environmental remediation and energy provision via H2 O2 production using ZnO–C with high reusability. The techno-economical aspect of H2 O2 photoproduction using ZnO–C is provided.